Hệ vi sinh vật có khả năng phân giải cellulose trên địa bàn tỉnh Thừa Thiên Huế - Phạm, Thị Ngọc Lan (Bộ Giáo dục và Đào tạo, 2013)
From soil, mud and humus - waste, we have isolated 105 trains Molds, 102 strains Strptomyces and 130 strins Bacterium and selected some strains with the haighest cellulolytic activity. We have also found out the suitable cultural conditions for these strains to syntheize cellulase.